Astrocytes and Microglia Exhibit Cell-Specific Ca2+ Signaling Dynamics in the Murine Spinal Cord - Rieder, Phillip; Gobbo, Davide; Stopper, Gebhard; Welle, Anna; Damo, Elisa; Kirchhoff, Frank; Scheller, Anja (Frontiers in Molecular Neuroscience, 2022)
The spinal cord is the main pathway connecting brain and peripheral nervous system. Its functionality relies on the orchestrated activity of both neurons and glial cells. To date, most advancement in understanding the spinal cord inner mechanisms has been made either by in vivo exposure of its dorsal surface through laminectomy or by acute ex vivo slice preparation, likely affecting spinal cord physiology in virtue of the necessary extensive manipulation of the spinal cord tissue. This is especially true of cells immediately responding to alterations of the surrounding environment, such as microglia and astrocytes, reacting within seconds or minutes and for up to several days after the original insult. Ca2+ signaling is considered one of the most immediate, versatile, and yet elusive cellular responses of glia. Here, we induced the cell-specific expression of the genetically encoded Ca2+ indicator GCaMP3 to evaluate spontaneous intracellular Ca2+ signaling in astrocytes and microglia. Ca2+ signals were then characterized in acute ex vivo (both grey and white matter) as well as in chronic in vivo (white matter) preparations using MSparkles, a MATLAB-based software for automatic detection and analysis of fluorescence events. As a result, we were able to segregate distinct astroglial and microglial Ca2+ signaling patterns along with method-specific Ca2+ signaling alterations, which must be taken into consideration in the reliable evaluation of any result obtained in physiological as well as pathological conditions. Our study revealed a high degree of Ca2+ signaling diversity in glial cells of the murine spinal cord, thus adding to the current knowledge of the astonishing glial heterogeneity and cell-specific Ca2+ dynamics in non-neuronal networks.